Impacto da expansão urbana sobre a Bacia do Córrego das Guaribas, setor sudoeste da cidade de Uberlândia-MG: uma análise de sua vulnerabilidade ambiental - Pavanin, Erich Vectore (2014)
This study was carried out to characterize and define the degree of environmental vulnerability, caused by urban sprawl in the watershed of the stream Guaribas in Uberlândia - MG. At first, we identify the physical attributes of the basin, through analysis of satellite images and field visits, as well as defining the dynamics of the use and occupation of land, to enable the assessment of whether the use of compliance with the environment and the type of relief, soils and rock materials found within the basin area legislation. The basin covers part of the urban and rural area of Uberlândia - MG. The analysis of land use in the years 1979, 1997, 2007, 2009, 2011 and 2013 indicated that the natural vegetation lost ground initially for agriculture and later agriculture has lost ground for grazing, and this is the type of use and predominant occupation within the limits of the basin today. With regard to urban sprawl , we found that since 1979 , some areas of the basin , were already being prepared for such use; in 1997 the urban occupation became the third type of use and occupation of most identified soil within the basin area and the second , from 2007. Environmental vulnerability maps indicated that, overall, the basin of the stream of howlers, with its distinctive natural features, has a predisposition to relatively high levels of vulnerability, which were intensified by human presence near the stream.